On 4-transitivity in the Moufang plane - Ciftci, Suleyman; Kaya, Rustem; Ferrar, Joseph C. (Birkhäuser-Verlag, 1988)
The purpose of this paper is to give a short proof of 4-transitivity in Moufang planes. This proof originated in the observation of the two first name authors that the standard Moufang identities, together with the identity (1) x?-1(y(xz)) = (x-1(yx)z, which is asserted in [2, p. 103] to hold in Cayley-Dickson division algebras, can be applied to give a particularly simple algebraic proof of the fact that the collineation group of a Moufang plane is transitive on four-points. Unfortunately, as pointed out by H. Karzel and demonstrated here in Proposition 1, (1) does not hold in Cayley-Dickson algebras. Nevertheless, the algebraic proof of transitivity remains valid after slight modifications and is given here as Theorem 1. © 1988 Birkhäuser Verlag.